Transformasi Kepemimpinan dan Budaya Organisasi: Implikasinya terhadap Kinerja Karyawan - Sulastri Oktavia (CV. ULIL ALBAB CORP, 2024)
Currently, various leadership styles and organizational cultures are applied in companies, including PT Semesta Abadi. Leadership is the art and process of influencing a group of people to work hard to achieve group goals. This process is a determining factor for the running of an organization or company. Through the leadership process, a leader can influence employees so that they can improve their performance in order to achieve company goals. This study aims to determine the impact of Leadership Style and Organizational Culture on PT Semesta Abadi. The research method used is a descriptive and verification research method, with a sample of 74 respondents who are employees of PT Semesta Abadi. Data collection was carried out by distributing questionnaires and data analysis using SPSS version 26. Based on the results of the study, Leadership Style and Organizational Culture have a significant effect on Employee Performance. Partially, leadership style has a very significant effect on employee performance, as well as organizational culture which also has a very significant effect on employee performance.